Optimization of immobilization conditions for protease extracted from torpedo scad (megalaspis cordyla) viscera using response surface methodology (RSM) / Normah Ismail and Syafiqah Naziha - Ismail, Normah; Naziha, Syafiqah (Universiti Teknologi MARA, 2019)
Protease was extracted from the viscera of torpedo scad fish (Megalspis cordyla) to obtain the crude extract which was then partially purified in 70% ammonium sulphate. The collected precipitate was dialysed and subsequently immobilized in sodium alginate and calcium chloride solution. The optimum concentrations of sodium alginate and calcium chloride to produce the highest yield of immobilized protease was determined by using Response Surface Methodology (RSM). From the results, the optimum conditions obtained were 2.5% of sodium alginate and 0.25 M of calcium chloride achieving a yield of 55.52%. Thus, the utilization of 2.5% sodium alginate and 0.25 M calcium chloride as the immobilization media were able to produce yield of immobilized protease from torpedo scad viscera with the highest proteolytic activity.